White men can't jump [videorecording (DVD)] - Snipes, Wesley; Harrelson, Woody; Perez, Rosie; Shelton, Ron, 1945- (20th Fox Century Home Entertainment, 2000)
Billy Hoyle and Sidney Deane are an unlikely pair of basketball hustlers. They team up to con their way across the courts of Los Angeles. Together, they play a game that's fast and dangerous.